Epidemiological Study of Hepatitis B, C and HIV Cases among the Foreigners Visiting Sulaimani City from 2013 Through 2016 - Mohammed Omer Mohammed; Asan Baram Hasan; Fenk Bakir Maarouf (Kurdistan Journal of Applied Research, 2019)
Hepatitis B, C and HIV infections present a great public health problem worldwide. More than 350 million of world's populations have chronic HBV infection and near 1 million people are dying due to this infection each year. About 150-200 million of world's population have chronic HCV infection that leads to nearly 350 000 deaths annually. On the other hand HIV remains as a major global public health issue. In 2015, about 36.7 million people were living with HIV and 1.1 million people died of HIV related illnesses.